The Clinical and Biomechanical Performance of All-Suture Anchors: A Systematic Review - Selim Ergün, M.D; Umut Akgün, M.D; F. Alan Barber, M.D; Mustafa Karahan, M.D (Elsevier, 2020)
Purpose: This systematic review aimed to clarify the relative strengths and weaknesses of the all-suture anchors (ASAs) in both clinical and experimental studies. Our hypothesis was that there would be similar clinical and experimental data for ASAs regarding the biomechanical properties, clinical outcomes and complication rates. Methods: A systematic review of MEDLINE and Embase databases was performed. The inclusion criteria for clinical studies were both retrospective or prospective study design and minimum 1-year follow-up; for biomechanical studies, the inclusion criteria were performance on either cadaver and animal bones or synthetic surfaces. Studies were excluded if the studies were not in English or if they were review articles, commentaries, letters, case reports, or technical notes. The risk of bias assessment was done using the Methodological Index for Non-randomized Studies (MINORS) tool. Results: We included 13 experimental and 3 clinical studies. The least displacement under cyclic loading was recorded with Q-Fix. Failure mode was mostly by suture breaking for the Q-Fix, whereas anchor pullout was the most common for the others. Cadaver humerus' greater tuberosity seemed to be less durable for the ASAs. Tests on cadaver glenoid showed similar biomechanical properties when compared to a control anchor. Studies investigating clinical and radiologic findings were very few, and only 3 case series were included in this review. Clinical findings of patients treated with ASAs for instability and rotator cuff repair showed satisfactory results and little increase in the complication rate (retear or revision surgery because of loose anchor). Conclusions: ASAs have similar or better biomechanical properties compared to regular anchors. Low-profile design seems to be an important advantage. Case series can not distinguish between the possible clinical benefits and/or risks. Clinical Relevance: ASAs have similar biomechanical properties when compared with other types of anchors. Their strength and performance vary with anatomic location, which may influence clinical success.